Taking their destiny in their hands: Social media, youth participation and the 2015 political campaigns in Nigeria (2018)
The issue of youth participation in political activities, including campaigns, has dominated scholarly discourse across the globe. The youth’s seeming apathy towards politics has continued to resonate among researchers, policy makers and other stakeholders. However, the emergence of social media has opened up new frontiers for citizens, especially for youths who are known to be social media savvy, to engage in political participation. This study investigated the relationship between social media use and University of Ibadan students’ participation during Nigerian political campaigns in 2015. Anchored on the uses and gratification theory, the study used a survey and focus group discussions (FGD) as the research design. Respondents, systematically selected (N = 588) took part in the survey while discussants, purposively selected (N = 24) participated in the FGD. Results revealed that cognitive, social and tension-free needs were motivations for using social media during the 2015 political campaigns by the respondents. Results also showed that there is a significant relationship between social media exposure patterns and students’ participation during the 2015 political campaigns. These results provide an important window of understanding on the relationship between social media use and political participation amongst Nigerian university students and have implications for the political development of Nigeria.